INFORMATION ABOUT AUTHORS - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2015)
VANDA ARAMAVIČIŪTĖ – habilitated doctor of social sciences (education), professor at the Department of Education, Vilnius University. Research interests: general educology, education and spiritual development of a personality, methodology of educational research. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: aramaviciute@gmail.com RŪTA BIKULČIŪTĖ – master of education. Research interests: education policy, education management, economics of education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: ruta.bikulciute@gmail.com AUDRA BALUNDĖ – master student of psychology, Department of Developmental and Educational Psychology, Lithuanian University of Educational Sciences. Research interests: psychology of creativity, organizational psychology. Address: Studentų Str. 39, LT-08106 Vilnius, Lithuania; e-mail address: audra.balunde@stud.leu.lt JŪRATĖ ČESNAVIČIENĖ – doctor of social sciences (educational science), lecturer at the Department of Health and Physical Education, Faculty of Sports and Health Education, Lithuanian University of Educational Sciences. Research interests: health education. Address: Studentų Str. 39, LT-08106 Vilnius, Lithuania; e-mail address: jurate.cesnaviciene@leu.lt LILIJA DUOBLIENĖ – doctor of social sciences (education), professor and Head of the Education Department, Vilnius University. Research interests: education philosophy, education policy, multicultural education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: lilija.duobliene@fsf.vu.lt RŪTA GIRDZIJAUSKIENĖ – doctor of social sciences, professor at the Music Theory and Education Department, Faculty of Art, Klaipeda University. Research interests: creativity development, music education, teacher training. Address: 4 K. Donelaičio Str.; e-mail address: ruta.girdzi@gmail.com SANDRA KAIRĖ – doctoral student of social science (education) at the Department of Education, Vilnius University, Lithuania. Research interests: intercultural education, learning through experience, non-formal education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; E-mail address: sandra.kaire@fsf.vu.lt DAIVA GRAKAUSKAITĖ KARKOCKIENĖ – doctor of social science (psychology); associate professor at the Department of Developmental and Educational Psychology, Lithuanian University of Educational Sciences. Research interests: psychology of creativity, family psychology, psychological counseling. Address: 39-328 Studentų Str., LT-08106 Vilnius, Lithuania; e-mail address: daiva.karkockiene@leu.lt VIDA GUDŽINSKIENĖ – doctor of social sciences (education), professor of the Institute of Educology and Social Work, Social Technology, Mykolas Romeris University. Research interests: health protection, promotion and (self-)education, modelling of educational process, (self-)development of life skills, expression of different student competences; development of social competences; social worker and teacher training. Address: 20 Ateities Str., LT-08303, Vilnius, Lithuania; e-mail address: vida.gudzinskiene@mruni.eu ZITA NAUCKŪNAITĖ – doctor of social sciences (education), associate professor at the Department of Lithuanian Language and Literature Didactics, Lithuanian University of Educational Sciences. Research interests: argumentation theory, rhetoric, language didactics, assessment. Address: 31 Ševčenkos Str., LT-03111 Vilnius, Lithuania; e-mail address: zita.nauckunaite@leu.lt SANDRA RIMKUTĖ JANKUVIENĖ – doctoral student (social sciences) of Klaipeda University, Lecturer at the Music Theory and Education Department, Faculty of Art, Klaipeda University. Research interests: musical creativity development, ICT and music education. Address: 4 K. Donelaicio Str., Klaipėda, Lithuania; e-mail address: sandra.rimkute.jankuviene@gmail.com IRENA STONKUVIENĖ – doctor of social sciences (education), associate professor at the Education Department, Vilnius University. Research interests: educational anthropology, history of education, cultural education, gender studies. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: irena.stonkuvienė@fsf.vu.lt RIMANTAS ŽELVYS – habilitated doctor of social sciences (education), professor at the Department of Education, Vilnius University. Research interests: education policy, education management, higher education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: rimantas.zelvys@leu.lt SNIEGUOLĖ VAIČEKAUSKIENĖ – doctoral student at the Education Science Faculty, Lithuanian University of Education; head of the External Evaluation of School Performance Quality Division, National Agency for School Evaluation. Research interests: moral education of younger teenagers, external evaluation of general education schools performance quality. Address: 82 Didlaukio Str., LT-08303 Vilnius, Lithuania; E-mail address: snieguole.vaicekauskiene@nmva.smm.lt